Registered Nurses: Who are they and what do they want - Preston, Alison (National Institute of Labour Studies, 2005)
Using 1981 and 2001 Census data together with primary data from a 2002 survey of Registered Nurses (RNs) in Western Australia, this paper profiles the nurse workforce. Amongst other things the paper reports on a high level of pay dissatisfaction, particularly amongst younger nurses. Hours of work also emerge as an important issue, with many RNs employed on a part-time basis and many more indicating they would prefer to work fewer rather than more hours. The demands of work and family are shown as impacting on these preferences, with 30.6 per cent of RNs reporting difficulty in balancing these conflicting demands. In the absence of any renewal strategy, the average age of nurses continues to rise. This age structure will change as RNs retire; one-third of all RN respondents to the 2002 survey plan on leaving the profession before 2008. A sizeable proportion of those who plan to leave are in the 26-30 age groups. The paper should sound a number of alarm bells for those engaged in nurse workforce planning.